Identification of HSP90 as a direct target of artemisinin for its anti-inflammatory activity via quantitative chemical proteomics. Issue 28 (2nd July 2019) - Wu, Guolin; Cheng, Bao; Qian, Hui; Ma, Shengming; Chen, Qin
Abstract : Global profiling of the target proteins of ART for its anti-inflammatory activity via ABPP combined with quantitative chemical proteomics. Abstract : The anti-malarial drug artemisinin (ART) possesses potent anti-inflammatory activity, yet its underlying mechanism of action has remained elusive. Here we employed quantitative chemical proteomics to in situ profile the cellular targets of ART and identified heat shock protein 90 (HSP90) as a direct target. Further study revealed that ART suppressed the production of nitric oxide (NO) in macrophages via inhibiting the interaction between HSP90 and inducible NO synthase (iNOS).